Florestas de mangue em diferentes condições ambientais sob o enfoque da estrutura vegetal, da biomassa e do estoque do carbono acima do solo no Mosaico de Áreas Protegidas do Lagamar - Chiquetto, Leticia Noveleto [UNESP] (Universidade Estadual Paulista (Unesp), 2024)
Mangroves are coastal ecosystems that offer a series of ecosystem services to humanity, including the sequestration of atmospheric carbon during photosynthesis. This process is known as “Blue Carbon” which is the term used to describe carbon captured, stored, and released mainly in marine-coastal ecosystems, an important factor in mitigating and adapting to climate change. The present study analyzed and compared the structural development and evaluated the carbon stock in the aboveground biomass (AGB) of mangroves under different environmental conditions on the southern coast of São Paulo and on the coast of Paraná, areas that are part of the Lagamar Mosaic of Protected Areas. For this purpose, the measurements of height, diameter at breast height (DBH), and identification of mangrove species were obtained in 52 permanent plots. From the data collected in the field, necromass and AGB were calculated using specific allometric equations. Based on these data, it was observed that the Iguape forests close to Icapara are in a good state of conservation and have high structural development, however, those close to the Valo Grande channel have high values of dead trunks and intermediate development. The Cananéia mangroves are in a good state of conservation with some forests being affected individually by natural events, with high development. The mangroves on the Paraná coast are in a good state of conservation, with low numbers of dead trunks and intermediate structural development. The Iguape forests have an average aerial biomass of 130.4 t/ha, resulting in an average carbon stock of 63.4 tC/ha and an average necromass of 21.3 t/ha. The areas in Cananéia have an average biomass of 196.3 t/ha, carbon stock of 86.3.1 tC/ha and an average necromass of 26.0 t/ha. Meanwhile, the forests of Paraná have an average biomass of 86.85 t/ha, of carbon stock of 38.1 tC/ha and an average necromass of 14.8 t/ha. The study demonstrates that the carbon stocks of mangrove forests in Iguape and Paraná are below the global averages and the Brazilian average. The data also shows that Cananéia has a carbon stock above the global and national averages. Although the mangroves in the study area are well preserved, those close to the artificial channel were impacted, showing a reduction in biomass, and consequently a reduction in carbon stock. These results show the importance of the need for programs and public policies for the conservation of mangroves and for the reduction of anthropogenic impacts on this ecosystem.

Os manguezais são ecossistemas costeiros que oferecem uma série de serviços ecossistêmicos à humanidade, entre os quais está o sequestro de carbono atmosférico durante a fotossíntese. Esse processo é conhecido como “Carbono Azul” que é o termo utilizado para descrever o carbono capturado, armazenado e liberado principalmente em ecossistemas marinhos-costeiros, um importante fator na mitigação e adaptação às mudanças climáticas. O presente estudo analisou e comparou o desenvolvimento estrutural e avaliou o estoque de carbono na biomassa aérea de florestas de mangue sob diferentes condições ambientais no litoral sul de São Paulo e no Paraná, áreas integrantes do Mosaico de Áreas Protegidas do Lagamar. Para tanto, foram obtidas medidas de altura, diâmetro à altura do peito (DAP) e identificação de espécies de mangue em 52 parcelas permanentes. A partir dos dados coletados em campo foram realizados os cálculos de biomassa e necromassa aéreas utilizando equações alométricas. A partir desses dados observou-se que as florestas de mangue em Iguape próximas de Icapara apresentam-se em bom estado de conservação e alto desenvolvimento estrutural, porém aquelas próximas ao canal do Valo Grande apresentam altos valores de troncos mortos e desenvolvimento intermediário. As florestas de Cananéia estão conservadas com algumas florestas sendo afetadas isoladamente por eventos naturais e com alto desenvolvimento. Os manguezais do litoral do Paraná apresentam-se em bom estado de conservação, com baixos valores de troncos mortos e desenvolvimento estrutural intermediário. As florestas de mangue em Iguape possuem média de biomassa aérea de 130,4 t/ha, resultando uma média de 63,4 tC/ha de estoque de carbono e média de necromassa de 21,3 t/ha. As áreas em Cananéia possuem média de biomassa de 196,3 t/ha e 86,3,1 tC/ha de estoque de carbono e média de necromassa de 26,0 t/ha. Enquanto as florestas do Paraná possuem média de biomassa de 86,85 t/ha e 38,1 tC/ha de estoque de carbono e com média de necromassa de 14,8 t/ha. O estudo demonstra que os estoques de carbono das florestas de mangue em Iguape e Paraná estão abaixo das médias globais e da média brasileira. Os dados também mostram que Cananéia possui estoque de carbono acima das médias globais e nacionais. Embora os manguezais da área de estudo estejam bem conservados, aqueles próximos ao canal artificial têm sido impactados, apresentando redução da biomassa, e por consequência redução do estoque de carbono. Esses resultados mostram a importância da necessidade de programas e políticas públicas para a conservação dos manguezais e para a redução dos impactos antrópicos nesse ecossistema.
Mangrove forests in different environmental conditions with a focus on plant structure, biomass and above-ground carbon stock in the Mosaico de Áreas Protegidas do Lagamar
Keywords: Manguezais; Necromassa; Carbono; Áreas protegidas; Estrutura vegetal; Monitoramento